2020
DOI: 10.1016/j.celrep.2020.108456
|View full text |Cite|
|
Sign up to set email alerts
|

Rare Variant Burden Analysis within Enhancers Identifies CAV1 as an ALS Risk Gene

Abstract: Summary Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disease. CAV1 and CAV2 organize membrane lipid rafts (MLRs) important for cell signaling and neuronal survival, and overexpression of CAV1 ameliorates ALS phenotypes in vivo . Genome-wide association studies localize a large proportion of ALS risk variants within the non-coding genome, but further characterization has been limited by lack of appropriate tools. By designing and applying a pipeline to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Others have detected decreased Cav-1 transcript in degenerating neurons in postmortem human brains, 12 and a recent study out of the University of Sheffield revealed reduced Cav-1 expression and disrupted MLR in human samples as an ALS-associated risk variant. 32 Proteomics also did not detect any difference in the total TrkB, which is similar to our IB results. We also did not find a significant difference in total TrkB expression since the highly expressed Trun-TrkB dilutes any detectable change in fl-TrkB (Trun-TrkB is abundantly expressed and serves as a dominant-negative receptor).…”
Section: Discussionsupporting
confidence: 90%
“…Others have detected decreased Cav-1 transcript in degenerating neurons in postmortem human brains, 12 and a recent study out of the University of Sheffield revealed reduced Cav-1 expression and disrupted MLR in human samples as an ALS-associated risk variant. 32 Proteomics also did not detect any difference in the total TrkB, which is similar to our IB results. We also did not find a significant difference in total TrkB expression since the highly expressed Trun-TrkB dilutes any detectable change in fl-TrkB (Trun-TrkB is abundantly expressed and serves as a dominant-negative receptor).…”
Section: Discussionsupporting
confidence: 90%
“…they were not yet present in the DG databases used in the experiment. These were ATXN1 ( 61 ), ATXN3 ( 62 ), SCFD1 ( 62 ), CAV1 ( 63 ) and SPTLC1 ( 64 ). Only ACSL5 ( 62 ) and GLT8D1 ( 65 ) were not present among the predicted genes.…”
Section: Resultsmentioning
confidence: 99%
“…We filtered for rare, deleterious variants within KANK1 enhancer, promoter and coding regions based on evolutionary conservation, functional annotations and population frequency (Huang et al, 2017; Karczewski et al, 2020; Rentzsch et al, 2019; Ritchie et al, 2014) ( Methods ). Enhancer and promoter regions for KANK1 were defined as previously described (Cooper-Knock et al, 2020; Fishilevich et al, 2017). Enhancer and promoter regions were independently enriched with ALS-associated rare deleterious variants (P<0.05, SKAT; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ALS GWAS studies to date have lost power by considering genetic variants in isolation, whereas in reality, a biological system is the product of a large number of interacting partners (Li et al, 2019; Wang et al, 2011). Moreover, noncoding regulatory regions of the genome have been relatively neglected in efforts to pinpoint the genetic basis of ALS, despite their functional synergy with the coding sequence (Cooper-Knock et al, 2020; Wang et al, 2018). Indeed, GWAS studies have suggested that a significant proportion of missing heritability in ALS is distributed throughout noncoding chromosomal regions (Nicolas et al, 2018; van Rheenen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%